2022
DOI: 10.1371/journal.pone.0275624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dry eye symptoms and risk factors among medical students in Serbia

Abstract: Background Dry eye is a multifactorial disease defined less than 30 years ago. It is a relatively common disorder, affected by a number of well-known risk factors. Dry eye can be challenging to diagnose because of the possible discrepancy between patients’ symptoms and clinical signs, and its overlap with other ocular surface diseases. Literature-wise, dry eye is usually associated with age and therefore investigated within older populations. Recently, studies focusing on young adult and student populations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Nevertheless, the results of this study did not reveal any association between DED and regular use of tobacco products on a daily basis. Additionally, studies in Serbia [19] and Dubai [20] did not find a smoking habit to be a risk factor for DED among university students. Contrarily, studies on Malaysian [44] students showed a significant association between DED and smoking.…”
Section: Behavioral and Environmental Factorsmentioning
confidence: 85%
See 3 more Smart Citations
“…Nevertheless, the results of this study did not reveal any association between DED and regular use of tobacco products on a daily basis. Additionally, studies in Serbia [19] and Dubai [20] did not find a smoking habit to be a risk factor for DED among university students. Contrarily, studies on Malaysian [44] students showed a significant association between DED and smoking.…”
Section: Behavioral and Environmental Factorsmentioning
confidence: 85%
“…Extended use of DDTs is considered to be a key risk factor for DED, which has been confirmed by many studies conducted in various study populations [2,37,38], and also in students in other countries [18][19][20]32,33]. DDT use triggers impaired blinking patterns, leading to disturbed meibum distribution and reduced exposure of the eye surface to tear film, which causes ocular surface damage [11,37].…”
Section: Behavioral and Environmental Factorsmentioning
confidence: 93%
See 2 more Smart Citations
“…. Based on this result, the patients can be divided into the following categories: no symptoms of DE (0-12), mild symptoms of DE (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate symptoms of DE (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and severe symptoms of DE (33-100) [15]. The study adopted the standards used by other authors, who defined symptomatic DED as an OSDI score greater than 12 [13,16].…”
Section: (Sum Of Scores)×25 Number Of Quest Ions Answ Eredmentioning
confidence: 99%